Reconstruction of STEM-Based Learning Videos on Topics of Escherichia Coli Bacteria - Ino Angga Putra; Yati Ludiana; Anggun Wulandari (APPLICATION: Applied science in Learning Research, 2021)
The purpose of this development research is to determine the design and feasibility of STEM-based learning videos on Escherichia coli bacteria material. The type of research used is research and development (R & D) with a 4D development model. However, in this study, it was limited to 3D without the Dessiminase stage. The research subjects were students of the 6th semester biology education study program with a total of 7-10 students. The data used are quantitative data (validation questionnaire scores and student responses) and qualitative data (suggestions and comments from validators and students). Data retrieval using a material and media validation questionnaire instrument and student response questionnaires. The results obtained are the formation of a product in the form of STEM-Based Learning Videos on Escherichia coli Bacteria with the "Eligible" category where 69.4% for material validation and 70.2% for media validation. Meanwhile, for student responses, the percentage is 78% in the interesting category. This product is expected to help students in learning independently so as to support the improvement of learning outcomes and student interest in learning. In addition, this product can be a source of supporting learning in the learning process as well as a source of reference for the wider community.